1998
DOI: 10.1046/j.1440-1614.1998.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Access to methods of suicide: what impact?

Abstract: Suicide methods employed by young Australians are changing, with a disturbing rise in frequency of hanging and car exhaust suicides slightly offset by a decline in firearm suicides. Opportunities exist for further reducing firearm suicides and addressing exhaust suicides by practical measures. There are also obvious options for changing prescribing practices with respect to more lethal medications (e.g. tricyclic antidepressants). However, the rise in hanging seems problematic from this perspective and in need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 40 publications
2
65
0
1
Order By: Relevance
“…This is in contrast to developments in other countries such as Australia where there has been a decrease in such suicides [29]. The incidence of 18.1% of shooting suicides in Austria also seems high; in the USA shooting is the most prevalent method (correlated with huge numbers of guns kept in private households), but in England and Wales only 2.5% of all suicides are by shooting [17].…”
Section: Resultsmentioning
confidence: 90%
“…This is in contrast to developments in other countries such as Australia where there has been a decrease in such suicides [29]. The incidence of 18.1% of shooting suicides in Austria also seems high; in the USA shooting is the most prevalent method (correlated with huge numbers of guns kept in private households), but in England and Wales only 2.5% of all suicides are by shooting [17].…”
Section: Resultsmentioning
confidence: 90%
“…As far as we are aware, this is the first study to present such a detailed gender-and age-specific analysis in suicide methods over a recent period of time in Japan. For males of all ages, a trend analysis revealed that 1990-1994−4.0* 1994-19988.6* 1998−1.5* 2009-201111.5 1.1 Drowning 1990-1992−12.6* 1992-1999−0.5 1999-2011 between 1990 and 2011 three different periods could be identified: an almost flat period in the early 1990s, a period of sharp increase until the late 1990s, followed by an almost flat period in the 2000s. For females of all ages, three different periods could also be identified: a period of moderate decrease in the early 1990s, a period of sharp increase until the late 1990s, followed by a period of slight little increase after the year 2000.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong and consistent evidence from international studies that restricting access to specific methods can prevent suicides (Cantor & Baume, 1998;Yip et al 2012). Means restriction proves most effective when the method is common and highly lethal (Yip et al 2012).…”
Section: Implication For Suicide Preventionmentioning
confidence: 96%
“…Aufgrund der restriktiven Gesetze bezüglich des Waffenbesitzes in Deutschland mag dies jedoch auch an der geringen Verfügbar− keit der genannten Methode liegen [13].…”
Section: Materials Andunclassified